THERMAL MODELING OF SUBDUCTED PLATES: TEAR AND HOTSPOT AT THE KAMCHATKA CORNER - Davaille A.; Lees J.M. (My University, 2004)
Pacific plate subduction at the Aleutian–Kamchatka juncture, or corner, could be accommodated by either a large bend or a tear in the oceanic lithosphere. In this paper, we describe a number of observations which suggest that the Pacific plate terminates abruptly at the Bering transform zone (TZ). Seismicity shoals along the subduction zone from Southern Kamchatka (600 km) to relatively shallow depths near the Kamchatka–Bering Fault intersection (100–200 km). This seismicity shoaling is accompanied by an increase in the heat flow values measured on the Pacific plate. Moreover, unusual volcanic products related to adakites are erupted on Kamchatka peninsula at the juncture. Simple thermal modeling shows that a slab torn and thinner along the northern edge of the Pacific plate would be compatible with the observations. Delayed thickening of the lithosphere due to the Meiji–Hawaiian hotspot may be responsible for the required thinning.